A Formal Human Reliability Analysis of a Community Pharmacy Dispensing Procedure. (September 2017) - Zheng, Xi; Bolton, Matthew L.; Daly, Christopher; Feng, Lu
Medication errors in community pharmacies are a major threat to patient health and safety. Current experimental and observational studies are insufficient to address the medication error problem due to its complexity. Thus, we adapt a well-validated human reliability analyses (HRA) approach for use with the probabilistic model checking, to create and validate a formal approach that allows the analysts to predict medication error rates and explore interventions for different community pharmacy procedures. We use the method to analyze a common dispensing procedure of community pharmacies and compare our results to published error rates. Finally, we discuss our results and explore how our method could be further developed in the future.